Strategi Pengembangan Bisnis Ekspor Bumbu Makanan Olahan dengan Menggunakan Analisis Business Model Canvas (BMC) dan SWOT pada CV Restu Mande - Hasna Cahya Kamila; Eva Ervani (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This research was conducted to determine the appropriate CV Restu Mande business strategy design using strengths, weaknesses, opportunities and threats (SWOT) analysis and the Business Model Canvas (BMC) in achieving export targets. The method used in this research is a descriptive qualitative method. Data collection carried out in this research was interviews with the leadership of CV Restu Mande, observation both directly and indirectly, and documentation. The SWOT analysis carried out in this research produces a SWOT matrix as a recommendation for CV Restu Mande's business strategy. The results of the SWOT analysis, SWOT matrix, and proposed new Business Model Canvas at CV Restu Mande are that in the customer segments section, target consumers are added in the form of Indonesian communities abroad, in the channels section, websites, international e-commerce and overseas retail need to be added, in the customer relationship section, rewards need to be added for resellers, dropshippers and loyal customers, in the key resources section we need to add production facilities, in the key activities section we need to add more interesting and detailed marketing activities, in the key partnership section we need to add agent collaboration. or distributors, loyal customers, production partners, and international trade consultants or experts, and in the cost structure section it is necessary to focus on investment in production facilities.